From school-family partnerships to school segregation : a matter of social inequalities - Diogo, Ana Matias (2017)
In the last three or four decades the relationship between school and family, namely the development of school-family partnerships, has been recurrent and consensually identified as fundamental to improve education and to combat difficulties in the schooling process, such as school failure and dropout, affecting more deeply the disadvantaged social groups. One question we might ask is to what extent this type of intervention can counteract the configuration of inequalities that mark the relationship of the different social groups toward school, in the context of the new constraints and possibilities affecting the family's relationship with the school. We will reflect on these issues through literature review, highlighting empirical results from research on the relationship of families with schools, keeping in mind especially the Portuguese case. We start with the notion of school-family partnership and after that we approach its limits, directing the look to the outside of these partnerships, tackling the problem of social segregation of school populations.